Aspek Religius Islam dalam Syair-syair Lagu Album Semesta Bertasbih Ciptaan Opick - Sari, Faradilla Intan; Arief, Ermawati; Zulfadhli, Zulfadhli (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research is to describe (1) islam religious aspect about aqidah in rhymes of song in Semesta Bertasbih album by Opick, (2) islam religious aspect about syariah in rhymes of song in Semesta Bertasbih album by Opick, and (3) islam religious aspect about morals in rhymes of song in Semesta bertasbih album by Opick. This data research is about the rhymes of song in semesta bertasbih album by Opick. The finding of research is Islam religious aspect in rhymes of song in semesta bertasbih album by opick, among of them are aqidah, syariah, and morals.